The Effect of Adding Cement Waste on The Quality of Concrete Compressive - Asrul Majid; Hammam Rofiqi Agustapraja (Litbang Pemas - Universitas Islam Lamongan, 2021)
Infrastructure development is one of the important aspects of the progress of a country where most of the constituents of infrastructure are concrete. The most important constituent of concrete is cement because its function is to bind other concrete materials so that it can form a hard mass. The large number of developments using cement as a building material will leave quite a lot of cement bags.In this study, the authors conducted research on the effect of adding cement waste to the compressive strength of concrete. This study used an experimental method with a total of 24 test objects. The test object is in the form of a concrete cylinder with a diameter of 15 cm and a height of 30 cm and uses variations in the composition of the addition of cement waste cement as a substitute for fine aggregate, namely 0%, 2%, 4% and 6%. K200). The compressive strength test was carried out at the age of 7 days and 28 days.The test results show that the use of waste as a partial substitute for fine aggregate results in a decrease in the compressive strength of each mixture. at the age of 7 days the variation of 2% is 16.84 MPa, 4% is 11.32 MPa and for a mixture of 6% is 6.68 MPa. Meanwhile, the compressive strength test value of 28 days old concrete in each mixture decreased by ± 6 MPa. So the conclusion is cement cement waste cannot be used as a substitute for fine aggregate in fc 16.6 (K200) quality concrete because the value is lower than the specified minimum of 16.6 MPa.